Proposed Improvement of Work-Center Capacity in Aerospace Industry: A Case Study of AMC’s Aircraft Ramp-Up - Mutiara Khofifah; Gatot Yudoko (UNIVED Press, 2025)
An aerospace manufacturing company faced significant capacity overload challenges while ramping up narrow-body aircraft aerostructure production from 6 to 10 units per month. This study utilized a Capacity Requirements Planning (CRP) framework and mixed methods, combining qualitative analysis through Current Reality Tree (CRT) and Focus Group Discussions (FGDs), with quantitative analysis of capacity utilization. The findings reveal critical bottlenecks in work centers such as “Work Center A” and “Work Center B,” which initially operated above optimal load (165% and 119%, respectively). After implementing solutions such as workload redistribution, predictive spare part planning, and integrated scheduling, simulations showed utilization dropping to 73% and 65%, respectively. This paper recommends adopting predictive planning systems and cross-functional collaboration for sustainable production efficiency.